Student Evaluation of Faculty: View from the Court - Haskell, Robert E. (Education Policy Analysis Archives, 1997)
Though a controversial history of research on the reliability and validity of student evaluation of faculty (SEF) exists, it has not been typically viewed as an infringement on academic freedom, promotion, reappointment, and tenure rights. As a consequence, legal aspects of SEF are neither readily apparent, nor available. Unlike academic freedom, tenure, and other issues, which exist as legal categories, SEF as a category is virtually absent in legal compendia on higher education law. The question of its judicial standing is important to any suggestion of abridging faculty rights. In this second of four articles, legal rulings are categorized and abstracted verbatim from cases where SEF is integral to the denial of academic freedom, tenure, promotion and reappointment are reviewed and provide and provide an initial resource of legal ruling on SEF. Seventy-eight findings are summarized from the abstracted textual material.